Influence of Lead on the Interpretation of Bone Samples with Laser-Induced Breakdown Spectroscopy - Abdolhamed Shahedi; Esmaeil Eslami; Mohammad Reza Nourani (Journal of Spectroscopy)
This study is devoted to tracing and identifying the elements available in bone sample using Laser-Induced Breakdown Spectroscopy (LIBS). The bone samples were prepared from the thigh of laboratory rats, which consumed 325.29 g/mol lead acetate having 4 mM concentration in specified time duration. About 76 atomic lines have been analyzed and we found that the dominant elements are Ca I, Ca II, Mg I, Mg II, Fe I, and Fe II. Temperature curve and bar graph were drawn to compare bone elements of group B which consumed lead with normal group, group A, in the same laboratory conditions. Plasma parameters including plasma temperature and electron density were determined by considering Local Thermodynamic Equilibrium (LTE) condition in the plasma. An inverse relationship has been detected between lead absorption and elements like Calcium and Magnesium absorption comparing elemental values for both the groups.